Sistem Pendukung Keputusan Penilaian Kinerja Pegawai Kantor Kepala Desa Menerapkan Metode WASPAS - Rosdiana Rosdiana (Bulletin of Computer Science Research, 2025)
An agency cannot be separated from the role of human resources (HR) working in it. The quality of HR is one of the important factors that influences the increase in productivity and effectiveness of agency performance. However, in practice, the employee performance assessment process is often still carried out manually or based on subjective considerations, so that it has the potential to cause injustice in decision making. To overcome this problem, this study designed a decision support system (DSS) based on the [mention method, for example: Weighted Product, AHP, MOORA, or others] method to evaluate employee performance objectively and measurably. This method was chosen because it is able to compare a number of alternatives based on several predetermined criteria, such as discipline, responsibility, initiative, and cooperation. This system was designed using [mention tools or platforms if any, for example: Microsoft Excel, PHP, MySQL, etc.] and tested using employee data from related agencies. The test results show that the developed system can help decision makers in evaluating employee performance more quickly, objectively, and efficiently. With this system, it is hoped that the performance assessment process will be more transparent and accountable and can increase employee work motivation.